2018
DOI: 10.1016/j.bbr.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of distracting input

Abstract: We review a series of studies exploring distractor suppression. It is often assumed that preparatory distractor suppression is controlled via top-down mechanisms of attention akin to those that prepare brain areas for target enhancement. Here, we consider two alternative mechanisms: secondary inhibition and expectation suppression within a predictive coding framework. We draw on behavioural studies, evidence from neuroimaging and some animal studies. We conclude that there is very limited evidence for selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
141
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 143 publications
9
141
3
Order By: Relevance
“…One recent proposal is that this form of learned inhibition relies on expectation suppression, consistent with predictive processing models, that have recently gained a lot of scientific traction and stature . In these models, the brain continuously generates predictions about incoming sensory input based on learned regularities in the environment, and what is being fed up the hierarchy is not sensory input per se, but rather the mismatch between the brain's a priori predictions and the incoming input, or so‐called prediction errors.…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 96%
See 4 more Smart Citations
“…One recent proposal is that this form of learned inhibition relies on expectation suppression, consistent with predictive processing models, that have recently gained a lot of scientific traction and stature . In these models, the brain continuously generates predictions about incoming sensory input based on learned regularities in the environment, and what is being fed up the hierarchy is not sensory input per se, but rather the mismatch between the brain's a priori predictions and the incoming input, or so‐called prediction errors.…”
Section: Indirect Preparatory Distractor Suppressionmentioning
confidence: 96%
“…In contrast to the notion of direct working memory–based distractor suppression, it has also been suggested that suppression of distracting information may rely on mechanisms that render the representation of the target in working memory maximally distinct from that of the distractor, thereby indirectly decreasing the chance of distractor selection . In yet another account, distractor inhibition may bypass representation in working memory altogether, relying on expectation‐dependent suppression . Below, we discuss these different accounts of preparatory inhibition in more detail in light of the empirical literature to address the outstanding question if distractor inhibition can be implemented in advance, and if so, how and under what conditions?…”
Section: Preparatory Distractor Suppressionmentioning
confidence: 98%
See 3 more Smart Citations